Albania : 2001 Article IV Consultation and Review Under the Poverty Reduction and Growth Facility-Staff Report and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2001)
Sound macroeconomic management, supported by structural reform, has characterized Albania's performance under the current Poverty Reduction and Growth Facility (PRGF) arrangement, although poverty and emigration remain pervasive. Privatization is moving forward in the telecommunications sector and has largely been completed in the mining sector. Fiscal performance so far in 2001 has been in line with the budget. Executive Directors supported the fiscal policy framework for the remainder of 2001 and welcomed the ongoing improvements in revenue collection, supported by the authorities' efforts to strengthen tax and customs administration.